The separation between the verb and its object in the Holy Quran: An Analytical Rhetorical Study - Alsalimi, Abdurrahman Helal Abdurrahman (Arab Journal for Sciences and Research Publishing, 2019)
This research sheds light on the phenomenon of the separation between the verb and its object in the Holy Quran and I have stopped, within the framework of that, at the phenomenon of separation among linguists and rhetoricians, and then a discussion of the overlap of the separation with advancing, postponing, and addition, and then a discussion of the difference between separation and objection then talked about the difference between syntactic separation and rhetoric separation. After collecting many pieces of evidence, it became evident that this separation has precise illustrative connotations, unique rhetorical meanings, and that each context has its role in guiding the significance of the separator. The Quranic versified style has followed a miraculous course; its methods are varied, and its methods have differed that led to a great influence on the uniqueness and accuracy of its illustration and strength of its focus. The study relied on the descriptive inductive method.